Analisis Kelayakan Pengembangan Bisnis Sayuran Hidroponik (Studi Kasus Kebun Gizi Hidroponik Pondok Pesantren Hidayatullah Depok) - Suharno; Yusalina; Fadhillah, Muhammad Dzaki (Forum Agribisnis, 2024)
Hydroponic Nutrition Garden at Hidayatullah Islamic Boarding School Depok is a Corporate Social Responsibility (CSR) program of Kimia Farma that utilizes the potential of Islamic boarding schools to support the development of economic independence at Hidayatullah Islamic Boarding School Depok. The demand for hydroponic vegetables in this nutrition garden continues to increase, but the amount of production has not met this demand, therefore it needs development. The purpose of this research is to see the feasibility of the company after development. The method used in this research is to look at financial and non-financial aspects. The results of the analysis on non-financial aspects state that the development of a hydroponic vegetable business is feasible based on market, technical, management, legal, social, economic, cultural, and environmental aspects. Results of financial aspect analysis based on NPV with a value of Rp. 140,052,675 and Rp. 205,508,544, IRR with a value of 57% and 68%, Net B/C with a value of 6.43 and 6.96, Payback Period with a period of 1 year 8 months and 1 year 6 months, and Incremental Net Benefit with a value of Rp. 65,455,869 show that the business is feasible to run either without or with development.